Emotional intelligence of Singaporean undergraduates - Chan, Clare Chui May (2008)
Research indicate that for success at the highest levels in leadership positions, close to 90% is attributable to Emotional Intelligence(EI). The aim of our study is to determine the EI of Singaporean undergraduates who are currently studying in local and foreign universities.